ANALISIS PROFITABILITAS USAHATANI TANAMAN â€œDAUN GEDIâ€ (Abelmochus Manihot) DI KABUPATEN MINAHASA UTARA - Rinny Lontoh (Universitas Sam Ratulangi, 2018)
ABSTRACT Â The purpose of this research is to know the profitability of the leaf crops Gedi in north of Minahasa regency. This research carried out during three months start from May until July 2019. The sample of this research used simple random sampling method. The data collected in this research is primary data and secondary data. Primary data obtained from direct interview to ten farmers of the leaf crops Gedi, secondary data obtained from the agency that related with the research and through google searching to got scientific journal article and skripsi from another university that related with topic of research. The result of this research showed that crop farming of Tanaman (plant) Gedi generate profit about 66,43%. It means that if the the bussiness is able to sell production result, so the level of the profitability obtained from the sale is 66,43%. Key Words : Profitability, Gedi, North of Minahasa regency.